Koncepcja systemu motywowania w firmie X - Tracz, Ewa (The Concept of a Motivating System in X Company, 2008)
The article's goal is to present the concept of a motivating system in one of the Polish companies, and subsequent stages on a journey to the ultimate solution. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 243-252